The first case report of Paragonimus westermani infection diagnosed by transbronchial lung cryobiopsy. (March 2023) - Kim, Ka Eun; Jung, Sung Soo; Park, Hee Sun; Lee, Jeong Eun; Chung, Chaeuk; Kang, Da Hyun; Lee, Song-I; Koh, Jeong Suk; Park, Dongil
Highlights: Pulmonary paragonimiasis is a tricky disease to diagnose. Finding its eggs is important in diagnosing pulmonary paragonimiasis. Transbronchial lung cryobiopsy is likely to be a better diagnosing method. Abstract : We report a case of pulmonary paragonimiasis diagnosed by transbronchial lung cryobiopsy (TBLC). TBLC is likely to be a superior method to transbronchial forceps biopsy because TBLC can get larger specimens, resulting in a higher chance of containing the eggs. A male patient aged 57 years presented with hemoptysis and dyspnea on exertion. His initial chest computed tomography scans showed a cavitary nodule with a peripheral ground-glass appearance, leading to a prescription of an oral antibiotic, with an initial assumption of pneumonia. A follow-up chest computed tomography, however, revealed an appearance of a new nodule adjacent to the original nodule. TBLC and transbronchial forceps biopsy were done to rule out lung cancer and eventually, the eggs of Paragonimus westermani were found using TBLC. Praziquantel was prescribed, showing improvements in symptoms and chest X-ray findings. TBLC has more potential to be utilized as a diagnostic method than transbronchial forceps biopsy because it has a better chance to confirm pulmonary paragonimiasis, which can be initially suspected as pulmonary tuberculosis or lung cancer.